Local Cultural Transformations in the Development of Halal Tourism in Indonesia and Malaysia - Hendri Hermawan Adinugraha; Ferida Rahmawati; Rizky Andrean (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The phenomenon of local cultural transformation in halal tourism is a strategic issue worthy of research because it involves tension between the preservation of tradition and the standardization of global halal services. This study aims to explore how local cultural values in Indonesia and Malaysia are integrated with Sharia principles to create an authentic and sustainable tourism experience. The research gap lies in the lack of comparative studies examining the interaction between local culture and halal tourism. In contrast, previous research has tended to focus on certification aspects or tourist behavior. This study employs a qualitative approach with a literature review design, collecting data from scientific journals, research reports, and policy documents. These documents are then analyzed using content analysis techniques, which involve reduction, categorization, and thematic synthesis. The analysis results show that Indonesia emphasizes community participation and local cultural richness, while Malaysia excels in regulation, standardization, and global promotion through the “Muslim-Friendly Tourism” branding. These findings contribute theoretically to the role of selective acculturation and cultural hybridization in halal tourism, while offering a culture-based development model compatible with the demands of the Muslim tourist market. Abstrak: Fenomena transformasi budaya lokal dalam pariwisata halal menjadi isu strategis yang layak diteliti karena mengandung ketegangan antara pelestarian tradisi dengan standarisasi layanan halal global. Penelitian ini bertujuan untuk mengeksplorasi bagaimana nilai-nilai budaya lokal di Indonesia dan Malaysia diintegrasikan dengan prinsip syariah guna menciptakan pengalaman wisata yang autentik dan berkelanjutan. Gap penelitian ini terletak pada kurangnya studi komparatif yang mengkaji interaksi antara budaya lokal dan pariwisata halal, sementara riset sebelumnya cenderung berfokus pada aspek sertifikasi atau perilaku wisatawan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi pustaka, mengumpulkan data dari jurnal ilmiah, laporan riset, serta dokumen kebijakan, kemudian dianalisis menggunakan teknik analisis isi melalui reduksi, kategorisasi, dan sintesis tematik. Hasil analisis menunjukkan bahwa Indonesia menonjolkan partisipasi komunitas dan kekayaan budaya lokal, sedangkan Malaysia lebih unggul dalam regulasi, standardisasi, dan promosi global melalui branding “Muslim-Friendly Tourism.” Temuan ini memberikan kontribusi teoritis terkait peran akulturasi selektif dan cultural hybridization dalam pariwisata halal, sekaligus menawarkan model pengembangan berbasis budaya yang kompatibel dengan tuntutan pasar wisatawan muslim.